Seasonal and Altitudinal Diversity of Butterflies in Eastern Siwalik of Nepal - Bhusal, Daya Ram; Khanal, Bhaiya (Journal of Natural History Museum, 2009)
Study on butterfly diversity at Churiya range of eastern Nepal in winter and spring was conducted during December 1999 to May 2000. Collection sites ranged from < 250 to >1150 m in altitude where a total of 40 species of butterflies belonging to 28 genera and eight families were recorded. Both of seasonal and altitudinal effects on the abundance of butterflies were noticed in the area. Species richness increased with upcoming warmer spring days at low and midland areas while decreased in higher elevations. Key words: Altitudinal; diversity; seasonal; abundance; species richness Journal of Natural History Museum Vol. 23, 2008 Page 82-87